Vigilance : the life of William Still, Father of the Underground Railroad - Diemer, Andrew K. (Alfred A. Knopf, 2022)
"The remarkable and inspiring story of William Still, an unknown abolitionist who dedicated his life to managing a critical section of the Underground Railroad in Philadelphia--the free state directly north of the Mason-Dixon line--helping hundreds of people escape from slavery"--